27th Aerospace Sciences Meeting 1989
DOI: 10.2514/6.1989-158
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of flame blowout limits by the use of swirl

Abstract: The blowout limits of a number of swirl stabilized flames were measured and the trends are explained by applying the concepts proposed in recent flame blowout theories, which previously have been applied only to non-swirling flames. It is shown that swirl flame blowout limits can be compared to wellknown limits for non-swirling simple diffusion flames by using the proper nondimensional parameter, i.e., the inverse DamkohlerUnlike most previous work. four parameters were systematically varied: the fuel tube dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 12 publications
1
33
0
5
Order By: Relevance
“…Such a small change of swirl number cannot have significant influence, as demonstrated in the present simulation. Similar conclusions were also reported by [31].…”
Section: Experimental Specificationssupporting
confidence: 92%
“…Such a small change of swirl number cannot have significant influence, as demonstrated in the present simulation. Similar conclusions were also reported by [31].…”
Section: Experimental Specificationssupporting
confidence: 92%
“…The blow-out limits (i.e. air versus fuel bulk velocities) at both fuel rich and lean compositions in a swirl burner from the University of Michigan (without appreciable bluff body effects) were measured and it is found that the operating conditions for stable swirling flames were extended relative to the nonswirl counterparts, although the extent depends on the swirl number [21,22]. The results also showed that the compact and strongly recirculating flames, instead of lift-off, can only been observed close to lean blow-out [21].…”
Section: Introductionmentioning
confidence: 99%
“…These recirculation bubbles result in enhancement of fuel-air mixing that further results in reduction of flame length (nearly five-fold) compared to simple non-swirling flame jet [36e38]. Further, it has also been reported in the literature that the recirculation zone increases the stability of the swirling flame (nearly five times) than the corresponding non-swirling flame [32,39]. In some of the cases, lifted stable swirling flames were also observed at sufficiently high swirl intensities [40e42].…”
Section: Introductionmentioning
confidence: 94%